Individual training model of 9 weeks preparation period for European Championship in shooting - Masalskyte, V.; Skarbalius, A. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Loads influencing by preparation models make variation of performance model (Perl, Mester, 2001). The aim of study was to apply successfully used previous training model of shooters V.M. (3rd place - European junior championship 1997, Lithuanian team) in order to perform the best result in European Championship 2003. Methods On the basic previous training model (2002 September -2003 August) was used one alternative experiment during September-October-November 2003 (9 weeks), testing (Rika Home Trainer), and mathematical statistics for analyzes (x± SD). Training program (training time with cartridge and training time without cartridge) was registered. Results Preparing for 2002 (September) -2003 (August) competitions period results grew up six months and top results were achieved at the most important competitions. The trend line was polynomial (y = -0,0105x2 + 0,8884x + 363,38; R2 = 0,6786) (Fig. 1). There were applying nine weeks fragment of 2002-2003 year model preparing for European championship 2003 (November). There were thought that previously used three weeks model would be adequate to the identical weeks pause in August-September and results would vary similarly (Fig. 1). The results were not adequate applying the same training model in different preparation period (Fig. 2, 3). Discussion/Conclusion There were determining European championship 2003 performance model results variation correlation with time of preparation with cartridge (0,544) and without cartridge (0,525). Correlation allows proposing that essential influence had structure of program content. European championship results allowed affirming that influence on performance had training model and not enough experience of international competition (P<0.001). Non-adequate variation of results could influence not correctly taken and applied fragment of training model or the problem of dynamic character of interaction between training and performance models (Perl & Mester, 2001).